The anti-cancer activity and potential clinical application of rice bran extracts and fermentation products. Issue 31 (10th June 2019) - Yu, Yonghui; Zhang, Jingjie; Wang, Jing; Sun, Baogao
Abstract : Extracts and fermentation products of rice bran serve important roles in mediating inflammation, cell cycel, cell apotosis, and cancer prevention. Abstract : Rice bran is the main by-product of rice processing and contains approximately 64% of the nutrients in rice. Its various nutrient elements include rice bran proteins, oil, oryzanol, vitamins, polysaccharides, etc. The use of fermented technology can increase the content of bioactive peptides, promote the absorption efficiency, and further improve the functionality and added value of rice bran. In recent years, the nutritional value and function of the extracts and fermented products of rice bran have been emphatically studied. Rice bran extracts and fermentation products serve a critical role in the anti-inflammatory reaction, reducing the plasma lipid effect and increasing anti-cancer activity. Moreover, few review studies have been reported on the anti-cancer activity and potential mechanism of action of rice bran extract and its fermentation products. In this review, we focused on the anti-cancer function, mechanisms, and potential clinical usage of rice bran extracts and fermentation products in the adjuvant therapy of cancer patients.